A comparison of alternative selection methods for reporting spirometric parameters in healthy adults - Jennifer H. Therkorn; Daniella R. Toto; Michael J. Falvo (Scientific Reports, 2021)
Abstract Alternative methods have been proposed to report spirometry indices from test sessions (forced expiratory volume 1 s, FEV1; forced vital capacity, FVC). However, most use the American and European Societies’ standard (ATS/ERS) which stops sessions once a repeatability threshold is met which may not accurately represent intra-session variability. Our goal was to repeat trials beyond the repeatability threshold and evaluate alternative reporting methods. 130 adults performed spirometry across two visits. Spirometry indices were reported using the ATS/ERS standard and four alternatives. 78 participants (60%) had valid data for all methods and visits. Intra-session coefficients of variation were low (FEV1: 3.1–3.7%; FVC: 2.3–2.8%). Our four alternative methods yielded FEV1 and FVC values ≤ 0.08 L different from ATS/ERS standard, which is not clinically meaningful. Intraclass correlation coefficients were ≥ 0.97 indicating consistency across repeated measures. The smallest real differences ranged from FEV1: 0.20–0.27 L and FVC: 0.18–0.24 L indicating consistency and low measurement error. Overall, all methods for reporting FEV1 and FVC demonstrated similar measurement error, precision, and stability within- and between-visits. These results suggest that once ATS/ERS repeatability is achieved, which approach is used for reporting spirometric variables may be of low clinical significance in a healthy population.